A Solid Pseudopapillary Neoplasm of the Pancreas Associated With IgG4-Related Pancreatitis: A Case Report. (May 2017) - Hatano, Yuichiro; Kawashima, Keisuke; Iwashita, Takuji; Kimura, Masaki; Shimizu, Masahito; Hara, Akira
A solid and cystic pancreatic lesion was incidentally found in a 62-year-old woman on abdominal computed tomography. The lesion was diagnosed as a solid pseudopapillary neoplasm by using endoscopic ultrasound-guided fine needle aspiration, and the tumor was resected. Histologically, the tumor cells had relatively small, round nuclei and papillary-like architecture in a hemorrhagic background. On immunohistochemical examination, the tumor cells were diffusely positive for nuclear β-catenin and cytoplasmic CD10. In addition, typical histological findings of IgG4-related pancreatitis (obstructive phlebitis, storiform-type fibrosis, and abundant IgG4-positive plasma cell infiltration) were found in the surrounding stroma of the solid pseudopapillary neoplasm. Postoperative workup failed to detect any other sclerotic lesions or serum IgG4 elevation, suggesting that the patient had no evidence of IgG4-related disease. To avoid misdiagnosis of a combined pancreatic neoplasm and fibro-inflammatory lesion, pathologists should consider such situations and make a definitive diagnosis after careful observation of all pancreatic lesions.